Long non-coding RNA-mediated competing endogenous RNA regulatory network during flower development and color formation in Melastoma candidum - Li, Hui; Wang, Wei; Liu, Rui; Tong, Botong; Dai, Xinren; Lu, Yan; Yu, Yixun; Dai, Seping; Ruan, Lin (Frontiers in Plant Science, 2023)
M. candidum is an evergreen shrubby flower and is receiving increased attention in garden applications because of its superior adaptation ability in south China. However, scant attention is paid to its flower development and color formation process at the non-coding RNA level. In this study, we conducted lncRNA-seq, RNA-seq, small RNA sequencing (sRNA-seq), and extensively targeted metabolomes for three different flower developmental stages of M. candidum. Differentially expressed long non-coding RNAs (DElncRNAs), differentially expressed mRNAs (DEmRNAs), differentially expressed miRNAs (DEmiRNAs), and differentially synthesized metabolites (DSmets) among different flower developmental stages were obtained. By GO and KEGG analyses of genes and KEGG analysis of metabolites, some key genes and metabolites in flavonoid, flavone, anthocyanin, carotenoid, and alkaloid-related biosynthetic pathways or GO terms were identified. Three direct-acting models, including antisense-acting, cis-acting, and trans-acting between lncRNAs and mRNAs, were detected to illustrate the direct function of lncRNAs on target genes during flower development and color formation. A lncRNA-mediated regulatory network composed of DElncRNAs, DEmiRNAs, DEmRNAs, and DEmets was constructed to explore the indirect role of lncRNAs in the flower development process of M. candidum. Using correlation analyses between the DERNAs and DSmets within the ceRNA regulatory network, and verification trials of the ceRNA regulatory mechanism, the roles of lncRNAs in flower development and color formation of M. candidum were illustrated. Our research provided a foundation for improving and regulating flower color at the lncRNA level in M. candidum.